Ought sexual minorities to be recognized as prisoners of conscience? - Nielsen, Jytte; Wittenkamp, Hanne; Madsen, Mogens (1979)
"Jytte Nielsen; Hanne Wittenkamp; Mogens Madsen... et al. Fonds Suzan Daniel (FSD)"